A phase II study of the efficacy and safety of the MET inhibitor capmatinib (INC280) in patients with advanced hepatocellular carcinoma. (December 2019) - Qin, Shukui; Chan, Stephen Lam; Sukeepaisarnjaroen, Wattana; Han, Guohong; Choo, Su Pin; Sriuranpong, Virote; Pan, Hongming; Yau, Thomas; Guo, Yabing; Chen, Minshan; Ren, Zhenggang; Xu, Jianming; et al.
Background: The objectives of this phase II study were to determine the clinical activity of the MET tyrosine kinase inhibitor capmatinib (INC280) in patients with MET-dysregulated advanced hepatocellular carcinoma (HCC) and to assess the safety, pharmacokinetics, and correlation of biomarkers with the response. Methods: This phase II, open-label, single-arm study evaluated twice daily (BID) oral capmatinib in a dose-determining stage, utilizing a Bayesian Logistic Regression Model (BLRM) subject to Escalation with Overdose Control criteria, safety, pharmacokinetics, and pharmacodynamic information to determine a recommended dose for expansion (RDE) evaluating efficacy in patients with MET-dysregulated HCC. Results: A total of 38 patients received treatment. In the dose-determining stage, patients received capmatinib 300 mg BID capsules ( n  = 8), and in the expansion, patients received 600 mg BID capsules ( n  = 28) or 400 mg BID tablets ( n  = 2) based on the BLRM and other relevant clinical data. No predefined qualifying adverse events (AEs) were observed during the first 28 days of treatment, and the RDE was 600 mg BID capsules (equivalent pharmacokinetics to 400 mg BID tablets). The most common any causality AEs were nausea (42%), vomiting (37%), and diarrhea (34%). In the expansion stage, in a subgroup of 10 patients with MET-high HCC, the overall response rate was 30%, including 1 durable complete response (>600 days) and 2 partial responses [1 durable (>600 days)]. Conclusions: Single agent capmatinib at the RDE is tolerable with a manageable safety profile. Antitumor activity was seen in a subset of patients with MET-dysregulated (MET-high) HCC. Trial registration: ClinicalTrials.gov: NCT01737827.https://clinicaltrials.gov/ct2/show/NCT01737827